Digital Divides or Dividends? Including Basic Services in Africa’s Digitalization Agenda: Evidence from Uganda - Mutenyo, John; Buyinza, Faisal; Ssenono, Vincent (INCLUDE, 2022)
Digital inclusion is about ensuring the benefits of the internet and digital technologies are available to everyone. Digitally excluded people can lack skills, confidence and motivation along with having limited or no access to equipment and connectivity. The major aim of this study was to undertake an in-depth country study to inform policy makers and development practitioners on the extent of digitalizing basic services in Uganda and its impact on inequality. The study further examines the access to basic digital services, usage, affordability, relevance and participation, in order to gain a holistic understanding of the inclusiveness of digital services in Uganda. Focus was placed on services between governments and citizens, as well as inter-governmental services, which help to increase the wellbeing of the poorest and most vulnerable groups, for example, households below the poverty line, rural populations, youth, women, and people with disabilities. This collaborative study was therefore set up: i) To take stock of digital basic service interventions in Uganda before and during the wake of the COVID-19 pandemic; ii) To assess how inclusive these interventions are in terms of reaching and improving the wellbeing of poor and vulnerable citizens; iii) To analyse progress in the enabling environment for inclusive digital transformation (including: physical infrastructure, digital skills, regulation, political economy, and institutional capacity) to see where efforts and investments could be prioritized and iv) to extract lessons and best practices for scaling digital basic services and making them more inclusive in order to reach and support those furthest behind. To achieve the purpose, the study employed a mixed methods approach involving desk review, secondary data analysis, qualitative and quantitative analyses derived from conducting Key Informant Interviews and a survey respectively. Several models were estimated on access to digital services, uses of digital services, frequency of internet use and affordability of internet using the Uganda National Household Surveys. Findings indicate that Uganda is progressing well in terms of policies and putting the necessary requirements in place to address the challenges of digital divide. This is premised on the fact that Uganda has establishment a data protection office, and it recently launched a portal at media centre for data controllers and processors and for individuals to register. More findings showed that some women do not use the internet because it lacks local content. The different digital uses include national online portal, utility payments, submitting income taxes, registering new businesses, applying for driving permits, applying for passports, payment for motor third party insurance, online birth registration, among others. The most commonly used digital service is mobile money, which is mostly used by individuals in the age group (25-64 years) which falls under working age. By region, central uses mobile money more than the rest of the regions. This is followed by the western, then the eastern and lastly the northern region. The study recommends that there is need for improved infrastructure investment in electrify connections especially in the rural areas, and expansion of 4G network to cover a large part of the country. These will in turn reduce the investment costs by the private telecom investors, and hence reduce user charges which is one of the key obstacles to solving the digital divide. Also increased awareness campaigns and sensitization to the public are necessary to spur and improve uptake and use of digital services. There is need for deliberate efforts to enhance the ability of Ugandans to acquire knowledge, skills and confidence to safely use digital products and services. Overall, policies should be holistic to include the practical implementation and regulation of new and existing digital services and ensure that they are not just available, but also relevant and useful for enhancing the wellbeing of all citizens.